Reproductive biology and some observation on the age, growth, and management of Tilapia zilli (Gerv, 1848) from Lake Timsah, Egypt - Waheed Farg-Alla Mahomoud; Amal Mohamed Mahmoud Amin; Kamal Fathey Elboray; Amal Mohamed Ramadan; Magdy Mostafa Kamal Osman EL-Halfawy (Advances in Aquaculture and Fisheries Management, 2018)
In the present investigation, some biological aspects of Tilapia zillii from Lake Timsah were studied. This was carried out on 700 fish samples collected during the period from October, 2002 to September, 2003. Total length of females ranged from 7 to 16 cm and males from 8 to 21cm. Age determination based on length frequency distributions showed that the life span are two and four years for females and males, respectively. Estimates of growth parameters are widely used for detailed assessment and modeling of fish species and fisheries. The lengthweight relationship, age at length zero (to), growth coefficient (K), asymptotic length (L∞) and rates of natural (M) and total mortality (Z) were estimated for T. zillii from Lake Timsah. Length-weight relationships were calculated from individual fish length and weight records collected from sampling using gill nets. Analyses were obtained by sampling direct from the fisher’s catches. Data were analyzed using the FISAT software. T. zillii, the estimate of K was 0.320 and 0.680 year-1 for males and females, respectively, whilst L∞ was approximately 22.05 and 17.85 cm, for males and females, respectively. T. zillii (males) had the lowest value of K and the largest L∞ than females. Natural mortality was the lowest for T. zillii (females) (M=0.464 and 0.38 year-1 ) and fishing mortality was highest for T. zillii (males) (F=2.656, 1.88 year-1 ). In addition, exploitation rate was estimated at E=0.83 and length at first capture (Lc) was calculated at 11.30 cm for males while E=0.78 and (Lc) was estimated as 6.68 cm for females. The majority of fish caught of the main commercial species in the Lake Timsah fishery were from the first age group, at a size far below the optimal length at capture. This suggests growth overfishing for T. zillii in Lake Timsah.